Modern forms of lectures on stochastics for students of economics universities (Pedagogy of Higher and Secondary Education, 2015)
Trunovа Ye. V., Tur A. I. Modern forms of lectures on stochastics for students of economics universities.In the article the modern educational technologies increasing efficiency of formation of stochastic competence of students of economic specialties are considered. The main areas ofstochastic training improvement of future economists are determined. The distribution of forms and methods to enhance the stochastics training process on topics is offered. The requirements for writing e-compendium in stochastics are defined. Functions of workbook in lectures are determined.
Keywords: stochastics; competence; future economists; educational technology; multimedia lecture; e-compendium